2006
DOI: 10.1007/s10695-005-5738-0
|View full text |Cite
|
Sign up to set email alerts
|

Serum biochemical parameters of Acipenser persicus

Abstract: Serum biochemical parameters are important aspects in the management of endangered species, such as Acipenser persicus. The values of these parameters can be used for confirming the maturity and for monitoring any changes in the quality of waters and related soils. Serum samples of 44 A. persicus fishes were analyzed and their serum parameter values were determined as Mean+/-SD in four groups: mature males and females and immature males and females, respectively. We compared the levels of calcium (Ca; 1.97 +/-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
33
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 18 publications
(15 reference statements)
4
33
3
Order By: Relevance
“…Mg levels were 1.15 and 1.51 mmol/l for great sturgeon females and males cultured for 3-4 years (Asadi et al 2009). Mg levels in juvenile great sturgeon in this study were lower than those of immature (2.74 mmol/l) and mature (3.05 mmol/l) Persian sturgeon A. persicus (Asadi et al 2006).…”
Section: Resultscontrasting
confidence: 68%
“…Mg levels were 1.15 and 1.51 mmol/l for great sturgeon females and males cultured for 3-4 years (Asadi et al 2009). Mg levels in juvenile great sturgeon in this study were lower than those of immature (2.74 mmol/l) and mature (3.05 mmol/l) Persian sturgeon A. persicus (Asadi et al 2006).…”
Section: Resultscontrasting
confidence: 68%
“…The results showed that mature females have higher AST and lower ALP and ALT activity than immature females, while mature males have higher ALP and lower ALT activities than immature males (Asadi et al 2006). Stellate is taxonomically placed between sharks and bony fishes, and there is a significant difference between this fish and sharks in terms of biochemical values.…”
Section: Discussionmentioning
confidence: 90%
“…Increased activity of AST indicated a high activity in the amino acid catabolism of liver (Asadi et al 2006). The value of AST is usually associated with the supply status of blood and oxygen in the liver.…”
Section: Resultsmentioning
confidence: 99%